The Influence Of Advertising Creativity, Brand Trust, And Brand Image On Consumer Purchase Intentions Of Cosmetic Products (A Study On Sociolla Store Users At Ska Mall Pekanbaru) - Armeilia Indah Azely; Syahdanur Syahdanur (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to understand the impact of advertising creativity, brand trust, and brand image on consumer purchasing interest in cosmetic products at the Sociolla Store, SKA Mall Pekanbaru. The development of digital economy has changed the way of trading, including in the cosmetic industry with the emergence of e-commerce platforms such as Sociolla. In the context of tight competition, understanding the factors that influence consumer purchasing interest becomes important. This study involved 120 respondents from Sociolla Store users at SKA Mall Pekanbaru. Data were collected using an online questionnaire assessing respondents' perceptions of advertising creativity, brand trust, brand image, and purchase interest. Data analysis was conducted using multiple regression to assess the influence of independent variables on the dependent variable. The results showed that the majority of visitors or consumers of Sociolla at SKA Mall Pekanbaru are individuals of relatively young age, especially in the age range of 26 to 35 years, with a background of higher education and diverse professions. Validity and reliability tests of the instrument showed that the questionnaire used has good validity and reliability. Data analysis showed that advertising creativity, brand trust, and brand image significantly influence consumer purchasing interest in cosmetic products. Advertising creativity plays an important role in attracting attention and influencing consumer purchasing interest. Brand trust also plays a role in forming long-term relationships between consumers and brands, while brand image creates unique perceptions and influences consumer preferences. In conclusion, advertising creativity, brand trust, and brand image have a significant influence on consumer purchasing interest in cosmetic products at the Sociolla Store, SKA Mall Pekanbaru. These results can be valuable guidance for cosmetic companies in enhancing their marketing strategies in the digital era